Study of Key Financial Activities as a Tool for Managerial Decision Making at PT MDM Indonesia Tbk - Fitri Purnamasari; Nurul Azizah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
As users of financial information, interested parties certainly need a variety of information to assess how well the company provides benefits for them, allows them to be invited to cooperate professionally, or has the potential to be given investment. Even internally, financial reports are also able to be a measuring tool to measure how well managers and employees have worked during the last period, so that the measurement of several key financial activities can be an evaluation tool that is very helpful for company managers. In this study, the company that is the object of research is PT MDM Indonesia, as one of the leading cosmetic manufacturers in Indonesia. From the results of the analysis, PT MDM Indonesia in 2014 obtained an RNOA of 14.20% of the average net operating assets of approximately 179 billion Rupiah, ROCE ratio of 14.58%, and an NBC value of -5.75% . This indicates that from the three perspectives, PT MDM Indonesia is considered to have high performance profitability and growth were quite good during the period from 2013 to 2014 then